THE ROLE OF FAMILY-BASED CHARACTER EDUCATION IN CHILDREN’S PERSONALITY DEVELOPMENT - St. Wardah Hanafie Das; Raden Muliana; Nur Aisyah Ustar; Abdul Assam (Journal International Inspire Education Technology, 2025)
Parents are obligated to teach noble morals to their children as the foundation of their personality development. Parents must be able to serve as role models and examples that can be imitated by children within the family environment. The family plays a very significant role in character education because children spend most of their time at home. The family becomes the first institution of character education before children receive formal education at school. Parents, especially mothers, have an undeniable role in educating children. The function of the mother as an educator within the family environment cannot be replaced, as the mother carries, gives birth to, and breastfeeds the child. For this reason, the mother is often referred to as the first and primary school for the child. Nevertheless, fathers also bear responsibility in educating their children. One of the most important factors determining the success of a child’s life is the effort made by parents. Therefore, parents must strive to create a peaceful and supportive atmosphere for their children. Providing enjoyable time together should not only involve staying at home but also engaging in enthusiastic learning processes through the use of various strategies. The success of children’s education greatly depends on the responsibility of parents in fulfilling their roles. The role of parents as motivators in shaping children’s character at home becomes a strategic effort in creating a learning process that encourages children to be active, enabling them to acquire attitudes and behaviors that continue to develop over time. Character education implemented from an early age within the family serves as a foundation for children’s future development. The family is also the first institution where children receive education and serves as a place for the growth and formation of children’s personality traits.